Development of landscape ecological model system using Bocopa monnieri, Lilaeopsis brasiliensis, Hemianthus callitrichoides and Glossostigma elatinoides for aquatic environment contaminants remediation - Anis Fatihah binti Abu Yazid (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
The pollution of aquatic ecosystems in Malaysia has emerged as a major ecological problem coinciding with rapid industrialisation and urbanisation. The contamination is caused predominantly by industries bearing heavy metals, such as Cd, Cr, Cu, Ni, and Pb which can cause significant ecological and environmental problems. Due to their high solubility in a water environment, they can easily enter the food chain, thus making it a serious health hazard for human and other organisms. Although conventional membrane filtration technologies are widely known as an alternative to treating the contamination, it is not always a convenient option due to its costly operations and maintenance. Presently, the study on phytoremediation using macrophytes is on-going and appears to be a prospective alternative and innovative technology that can be applied to contaminated aquatic environments. However, careful evaluation of its applicability and effectiveness will be required. Therefore, this study aims to assess Cd, Cr, Cu, Ni, and Pb remediation in water through selected aquatic plant species via the in-vitro model system. The study will assess four selected aquatic species, which are Bacopa monnieri, Lilaeopsis brasiliensis, Hemianthus callitrichoides and Glossostigma elatinoides. The four aquatic species have distinctive qualities which resulted in having different remediation rates and tolerance towards heavy metals in water. Metal characteristics, mixed metals interaction, pH and other environmental factors can also influence the remediation rate. Phytoremediation of the five heavy metals will be assessed within a mixed metals contamination model system in four different periods (week 1 until week 4) at three different concentrations (1ppb, 2ppb, and 5ppb). The findings indicate that all of the plant species have the capability to remediate all the heavy metals and Bacopa monnieri stood out as a species that can withstand and remediate heavy metals even at 4 weeks of exposure to heavy metals at all three concentrations. The highest recorded bioconcentration factor (BCF) was not the Bacopa monnieri sequestration rate, but Cd and Pb sequestration by Glossostigma elatinoides, which were 48.6 and 36.0 respectively. All of the plants may have shown vary signs of stress and symptoms of toxic poisoning due to high concentration level exposure to the heavy metals at extended periods. This study identified metal excluders and metal accumulators as the two main mechanisms of heavy metals uptake. For example, Bacopa monnieri and Hemianthus callitrichoides may have shown signs of tolerance mechanism, in which they both can accumulate heavy metals while maintaining it growth development by restricting metals translocation on their plant tissue, however there is a high heavy metal concentrate in their roots. Whereas, Glossostigma elatinoides and Lilaeopsis brasiliensis can accumulate significant amount of heavy metals but with lesser levels of tolerance towards higher concentrations of heavy metals. The expected outcome of this research is to introduce the potentials of phytoremediation as an innovative strategy to remediate aquatic environment contaminants.